HRM Practices and its Impact on Employee Performance: A Study on the Cement Industry in Bangladesh - Akhter, Mst. Momena; Siddique, Md. Nur-E-Alam; Alam, Md. Asraful (Global Disclosure of Economics and Business, 2013)
In present situation, companies can gain strong competitive advantage through applying effective and efficient human resource practices. If the human resources are managed properly, they can contribute to the success for the company. The effective management of human resource is possible through the implementation of sound HRM practices. . The main objective of this research is studying the impact of HRM practices on employee performance in the context of cement industry in Bangladesh.  For this purpose the researchers have tried to investigate impact of the various components of HRM practices on employee performance of a sample of 160 employees from seven cement companies listed in the Dhaka Stock Exchange. The data were analyzed by a regression analysis to determine the impact of HRM practices on employee performance. The result shows that training & development and opportunity for career development have a significant positive impact on employee performances. On the other hand, Performance appraisal, Compensation & Benefits, and Leadership Practices have a positive impact on employee performance but the impact is not significant in the context of cement industry in Bangladesh. Moreover, work life balance has a negative impact on employee’s performance. Furthermore, efficient management of human resources can increase the performance of the employees of the cement companies in Bangladesh.JEL Classification Code: M12; J53